2015
DOI: 10.1177/0971521514556944
|View full text |Cite
|
Sign up to set email alerts
|

Women Caregivers of Persons with Brain Tumour: A Psychosocial Needs Assessment in a Tertiary Care Hospital in Bangalore

Abstract: The diagnosis of a brain tumour poses severe challenges to patients as well as their caregivers. As caregivers, women play an important role. However, most of the literature on brain tumours has failed to emphasise the invaluable services of women caregivers, and their psychosocial needs have been overlooked. The current study aims to highlight this neglected aspect. Thirty women caregivers were selected through purposive sampling and their needs were assessed using a semi-structured questionnaire under five h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…The review by Thompson et al on psychosocial oncology stresses the effectiveness of psychosocial interventions during the course of illness . It was found that although reassurance was important in coping the illness, standard care seldom stressed the need for psychological care in the management and prevention of distress and promotion of well‐being . These findings are in keeping with those of the present study wherein the participants were hardly ever referred to a mental health professional for counselling despite the presence of the facility within the same hospital.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The review by Thompson et al on psychosocial oncology stresses the effectiveness of psychosocial interventions during the course of illness . It was found that although reassurance was important in coping the illness, standard care seldom stressed the need for psychological care in the management and prevention of distress and promotion of well‐being . These findings are in keeping with those of the present study wherein the participants were hardly ever referred to a mental health professional for counselling despite the presence of the facility within the same hospital.…”
Section: Discussionsupporting
confidence: 88%
“…Offspring, who were the caregivers, considered this to be a duty and privilege and an opportunity to express their gratitude to those who had supported them through their growing up phase. Literature on caregiving suggests that family, especially women, undertakes the responsibility of a sick individual, particularly psychological caregiving . In addition to women being the preferred caregiver, our study has distinctively demonstrated that caregiving was not limited to a woman centric activity and that spouses in general were perceived as better caregivers and equal number of men were involved in caregiving.…”
Section: Discussionmentioning
confidence: 62%
“…LGGs. The impact and potential support needs related to the fear and uncertainty of 'when' the tumour will progress (Amaresha et al, 2015) are distinct from the fear of 'if' the cancer will recur, experienced by ICs of people with cancers that have more favourable prognoses (Smith et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The incurable nature of LGGs meant our participants often described being in what could be considered a liminal state (Sabo, 2014), grieving a life they once had, with future plans disrupted by an undeterminable wait for an inevitable outcome; this presented what appeared to be the greatest source of emotional distress for ICs of people with LGGs. The impact and potential support needs related to the fear and uncertainty of ‘when’ the tumour will progress (Amaresha et al, 2015) are distinct from the fear of ‘if’ the cancer will recur, experienced by ICs of people with cancers that have more favourable prognoses (Smith et al, 2021).…”
Section: Discussionmentioning
confidence: 99%